Sustainable Retrofits in Existing Buildings Analysis of Stakeholder Types, Requirements, and Perceptions in Decision Making, using the House of Quality - Baer, Brad (My University, 2012)
There are multiple reasons why existing building stakeholders are concerned with increasing the sustainability of their buildings from social, environmental, economic, and technical perspectives. In most cases, these building stakeholders have varying and opposing perspectives on how, when, and why a building should be sustainably retrofitted. Several studies indicate that conflicting stakeholder requirements are a main barrier in implementing sustainable retrofits and that the decision is most often made based purely on short-term economic grounds. However, most studies did not take into account the important role that different building stakeholders play in determining the type and extent of any retrofit measures, or develop methodologies to fully enhance the interaction amongst these stakeholders which currently do not exist. This research presents a unique investigation into the challenges and barriers that are involved in meeting the various sustainable retrofit requirements of many different types of stakeholders. In this research, the effect of the stakeholder type and the hierarchy of their respective requirements in the decision to sustainably retrofit an existing U.S. Navy case study building were explored. A House of Quality (HOQ) model was developed through this research that synthesized differences amongst the many stakeholders, integrated their competing objectives, and a new way of analyzing HOQ data was introduced. This research demonstrated that a top-down owner commitment to sustainability was able to align the many competing stakeholder requirements and eliminate barriers that could potentially get in the way of efficient project decisions and results. The retrofit decision in this case study was based primarily on delivering economic impacts. However, the harmony between perceptions concerning social,environmental, and economic factors was not substantially out of balance and on the forefront of the policy that aligned the stakeholders.